Floridians’ Perceptions of GMOs: GMOs and Florida Citrus - Nicole M. W. Dodds; Laura M. Gorham; Joy N. Rumble (EDIS)
Worldwide and in Florida, food-related issues such as food safety, food security, and use of new food technologies continue to be top concerns. Among the food-related issues are concerns about consuming the products from transgenic plants, often referred to as “GMOs.” This 4-page fact sheet is intended to help Extension faculty understand public perceptions regarding the use of genetic engineering to combat citrus greening. Extension faculty can use this understanding of public perceptions as they develop and deliver programming for clientele. Written by Nicole M. W. Dodds, Laura M. Gorham, and Joy N. Rumble, and published by the UF Department of Agricultural Education and Communication, October 2014.